Предмет: Математика,
автор: ммоолоооооооррпр3
упростите выражение (7y-4) (2y+3) - 13 y
Ответы
Автор ответа:
0
(7y - 4)(2y +3) -13y =
+ 21y - 8y - 12 - 13y =
+ 21y - 21y -12 =
-12
Автор ответа:
0
помоги м другим
Автор ответа:
0
пж
Автор ответа:
0
5b+(a+5b) (ab-bво второй степен)
Автор ответа:
0
Щас решим
Автор ответа:
0
5b + (a^2b -ab^2 +5ab^2 -5b^3) = 5b + a^2b +4ab^2 - 5b^3 = b(5 +a^2 + 4ab - 5b^2)
Автор ответа:
0
Похожие вопросы
Предмет: Литература,
автор: Mirawithsemenowka60
Предмет: Алгебра,
автор: gorakondrat2009
Предмет: Математика,
автор: zagladkomaksim
Предмет: Математика,
автор: Arenos